2022
DOI: 10.1021/acsabm.2c00361
|View full text |Cite
|
Sign up to set email alerts
|

Graphdiyne Oxide Quantum Dots: The Enhancement of Peroxidase-like Activity and Their Applications in Sensing H2O2 and Cysteine

Abstract: As one of the typical carbon nanomaterials, graphdiyne (GDY) with unique chemical, physical, and electronic properties has a great potential in various fields. Although it is an important member of carbon nanozymes, the research on its intrinsic enzyme mimetic properties and applications is still limited. Herein, graphdiyne oxide quantum dots (GDYO QDs) have been synthesized through oxidative cleavage, which exhibit enhanced peroxidase-like activity with lower K m and higher V max than those of most carbon-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Though Sun et al reported the synthesis of GDY oxide QDs using nitric acid that exhibited peroxidase-like activity, the lack of radical scavengers on the QD surface might lower the detection performance. 31 As a result, this study reports, for the first time, the biomimetic nature of fluorescent GDY QDs that were prepared through a hydrothermal process. The present study has utilized the mimetic nature of GDY QDs (nanozymatic activity) for H 2 O 2 and dopamine detection.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Though Sun et al reported the synthesis of GDY oxide QDs using nitric acid that exhibited peroxidase-like activity, the lack of radical scavengers on the QD surface might lower the detection performance. 31 As a result, this study reports, for the first time, the biomimetic nature of fluorescent GDY QDs that were prepared through a hydrothermal process. The present study has utilized the mimetic nature of GDY QDs (nanozymatic activity) for H 2 O 2 and dopamine detection.…”
Section: Introductionmentioning
confidence: 88%
“…Hence, the research focus should be given to the nanomaterials’ size and surface functional group to achieve higher nanozymatic activity and better detection sensitivity. Though Sun et al reported the synthesis of GDY oxide QDs using nitric acid that exhibited peroxidase-like activity, the lack of radical scavengers on the QD surface might lower the detection performance …”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been developed to enhance the enzymatic activity of the GDY nanomaterial. For example, functional modification has been adopted to synthesize GDY-based nanozymes with high activity, including hemin- and metal-based nanozymes. , By changing morphological size, GDY oxide or GDY quantum dots with abundant C–O and CO bonds have shown high catalytic activity compared to the pristine GDY nanomaterial. , Doping of heteroatoms such as N, B, and S, , which can change the charge distribution of the GDY nanomaterial and increase the density of the active sites, has also been used to improve the activity of the GDY nanomaterial. Nevertheless, compared with other carbon nanomaterials, such as graphene, the study and application of GDY-based nanozymes are still in the initial stage.…”
Section: Introductionmentioning
confidence: 99%
“…Bai et al 26 prepared a GDYO QDs nanosensor to detect ascorbic acid. Guo et al 27 constructed a colorimetric sensor to detect hydrogen peroxide and cysteine based on GDYO QDs. However, the disadvantages of quantum dots have been plagued, such as low yield and low luminous efficiency.…”
Section: Introductionmentioning
confidence: 99%